2013
DOI: 10.1002/prep.201300053
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Porous Silicon as Nano‐Explosive Material

Abstract: It is a decade since the accidental discovery of the room temperature explosive properties of porous silicon, impregnated with a solid state oxidizer, was communicated in 2002 [1]. A significant amount of research and development have followed this announcement, leading to an innovative explosive technology that may be on the verge of being applied in a number of applications. It is thus now an opportune time to reflect on the progress of this new technology over the last decade. Just in the last two years, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Past studies have demonstrated that etch depth can have a significant effect on flame propagation 13, 16. These studies investigate moderate burn speeds up to 200 m s −1 for unconfined samples, showing that as etch depth decreases below 30 μm, so does the flame speed.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Past studies have demonstrated that etch depth can have a significant effect on flame propagation 13, 16. These studies investigate moderate burn speeds up to 200 m s −1 for unconfined samples, showing that as etch depth decreases below 30 μm, so does the flame speed.…”
Section: Resultsmentioning
confidence: 92%
“…A sample of images for flame speed analysis from Set 4 is given in Figure 2. In the past, potential errors have been noted for flame speed analysis due to inconsistencies or “jumps“ in the reaction front 16. In this study care was taken to analyze only steady propagation fronts, similar to that in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…The explosive behavior of pSi films, impregnated by an oxidizing agent, has been recognized and steadily investigated since 1992 [2].T he behavior originates from the very high internal surface area of pSi (in the order of 800 m 2 per gram) which permits av ery intimate mixture between the oxidizinga gent and the fuel (silicon), leading to materials that are stable at room temperature and are able to react explosively upon applicationo fa ne nergy stimulus. Indeed, pSi energetic materials prepared in this way are sensitive to aw ide variety of stimuli.…”
mentioning
confidence: 99%
“…Indeed, pSi energetic materials prepared in this way are sensitive to aw ide variety of stimuli. Methodso fi nitiation thath ave been reported include heating using for example ah otplate [3] or ah ot bridge-wire [4,5],m echanical stimulus (such as scratching the surface or light friction) [6],o rb y an electrical spark [6].A dditionally,l aser ignition of pSi energetic materials has been reported using av ariety of wavelengths and laser fluences [6][7][8][9].I th as also been observed in several reports that pSi energetic materials are highly sensitive to initiation by weak mechanical stimuli such as scratching or mechanical fracture [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation